2020
DOI: 10.3390/nano10030474
|View full text |Cite
|
Sign up to set email alerts
|

Fly Ash, from Recycling to Potential Raw Material for Mesoporous Silica Synthesis

Abstract: In order to meet the increasing energy demand and to decrease the dependency on coal, environmentally friendly methods for fly ash utilization are required. In this respect, the priority is to identify the fly ash properties and to consider its potential as raw material in the obtaining of high-value materials. The physico-chemical and structural characteristics of the fly ash coming from various worldwide power plants are briefly presented. The fly ash was sampled from power plants where the combustion of lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(44 citation statements)
references
References 41 publications
1
37
0
2
Order By: Relevance
“…Both being volatile in nature, a major amount of Hg and Cd are eliminated from the coal at the time of combustion in the furnace. Moreover, it has been found that smaller the size of fly ash particles higher will be the concentration of heavy metals on their surface i.e., larger fly ash particles will have lesser amount of heavy metals and other elements on their surface than the small-sized fly ash particles [69,70]. In a thermal power plant, there are two types of ashes; bottom ash and fly ash [71].…”
Section: Inductively Coupled Plasma Analysis Of Fly Ash Digested Samplementioning
confidence: 99%
“…Both being volatile in nature, a major amount of Hg and Cd are eliminated from the coal at the time of combustion in the furnace. Moreover, it has been found that smaller the size of fly ash particles higher will be the concentration of heavy metals on their surface i.e., larger fly ash particles will have lesser amount of heavy metals and other elements on their surface than the small-sized fly ash particles [69,70]. In a thermal power plant, there are two types of ashes; bottom ash and fly ash [71].…”
Section: Inductively Coupled Plasma Analysis Of Fly Ash Digested Samplementioning
confidence: 99%
“…The recent research studies have been performed for capitalization of fly ash by different methods, such as direct activation method [34,35,53,[58][59][60][61][62][63], fusion method [57,64,65], and microwave and ultrasound method [67]. Fig.…”
Section: Synthesis and Characterization Of Eco-friendly Nano-adsorbentsmentioning
confidence: 99%
“…The bulk form of fly ash can be potentially used as a biofertilizer, as it contains a rich source of plant nutrients such as, Na, Ca, K, P, Zn, Mg, Mn, Mo, etc. Moreover, the zeolites synthesized from fly ash can also be used for the sustained and controlled release of the N, P, K and other minerals to the plants [23,66]. In the field of agriculture, [67,68] the bulk fly ash can be used for resource conservation, reclamation of the contaminated sites and restoration of industrial sites [69].…”
Section: Applications Of Fly Ashmentioning
confidence: 99%
“…However, almost all the fly ash, irrespective of their origin, has almost all the above-mentioned minerals in variable amounts. Based on the mineralogy of fly ash, it can be a reliable and valuable alternative resource for the generation of ferrous, alumina and silica-based micro and nanoparticles [23]. Ferrous, alumina and silica generally co-exist in the fly ash (shown in Figure 4) as either ferro-alumino-silicates (FAS) or alumina, and silica can be present in the form of crystalline mullite, sillimanite or quartz [89,90].…”
Section: Fly Ash As a Source Of Ferrous Alumina And Silicamentioning
confidence: 99%